2013
DOI: 10.1590/s0036-46652013000500003
|View full text |Cite
|
Sign up to set email alerts
|

HIGH PREVALENCE OF Strongyloides stercoralis INFECTION AMONG THE ELDERLY IN BRAZIL

Abstract: SUMMARYLittle is known about the frequency of intestinal parasites in the elderly due to a lack of attention given to the occurrence of these infections among older adults. This study compares the frequency of Strongyloides stercoralis and other enteroparasites between elderly living in nursing homes (n = 100) and those noninstitutionalized (n = 100) from Uberlândia, state of Minas Gerais, southeastern Brazil, associated with data of epidemiological and socio-demographic conditions. Through coproparasitologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
(50 reference statements)
1
14
1
3
Order By: Relevance
“…The family income significantly associated with Strongyloidiases infection because the low income family gets more infection owing to their poor family status and unable to keep them in hygienic condition. One study in elderly of Brazil Showed significantly association of family income with Strongyloidises infection [33].…”
Section: Discussionmentioning
confidence: 99%
“…The family income significantly associated with Strongyloidiases infection because the low income family gets more infection owing to their poor family status and unable to keep them in hygienic condition. One study in elderly of Brazil Showed significantly association of family income with Strongyloidises infection [33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies to diagnose the incidence and/or prevalence of parasitic diseases at these institutions have been conducted over the years. For the diagnostic tests available and implemented so far, the results show that the prevalence of enteroparasites in the elderly is not associated with long-term institutions, sociodemographic characteristics, lifestyle, or health conditions [4,5]. However, the frequencies of enteroparasites in the elderly appear to be underestimated because they may vary depending on the study and the country/region evaluated.…”
Section: Introductionmentioning
confidence: 94%
“…Among the pathogenic helminths investigated, the one most often diagnosed is Strongyloides stercoralis (S. stercoralis), a nematode parasite that causes strongyloidiasis, a disease characterized by skin and digestive symptoms, in humans [1][2][3][4][5]. Parasitological surveys using more sensitive and rigorous techniques are needed to provide more reliable results and serve as the basis for future interventions involving sanitary and educational measures to improve health maintenance [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have identified an association between intestinal parasitosis in the elderly and socioeconomic factors (age 5 , marital status, education and income 25 ) and health conditions (activities of daily living 25 ), in the present study, no association was found with these groups of variables, although it was observed that older elderly people (OR=1.59), who live alone (OR=1.38), were illiterate or can read and write (OR=1.15), anemic (OR= 1.36), who reported a lack of appetite (OR = 1.44) or were dependent for IADL (OR=1.60) were more likely, although not significantly so, to be affected by intestinal parasitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Both measurements were performed in duplicate and the mean values were used in the analyzes. For analysis, BMI was categorized as underweight (BMI<22), normal weight (BMI of [22][23][24][25][26][27] and overweight (BMI>27Kg/m²) 8 .…”
Section: Methodsmentioning
confidence: 99%